Acerca de la diatomea Didymosphenia geminata (Lyngbye) M. Schmidt: su morfología y distribución en Chile - RIVERA, PATRICIO; BASUALTO, SILVIA; CRUCES, FABIOLA (Gayana Botánica, 2013)
The freshwater diatom Didymosphenia geminata was studied from Chilean material collected in Río Espolón and Río Bío- Bío using light and electron microscopy. Its principal morphological features are described and illustrated for the first time and comments about its relationships with other closely taxa, as well as its distribution in Chile, are given.